The Effect of Organizational Culture on Employee Performance Mediated by Work Motivation at PT. Permodalan Nasional Madani Cianjur Branch - Tarjono (PT. PENERBIT TIGA MUTIARA, 2024)
This study aims to examine the effect of organizational culture on employee performance through employee work motivation at PT. Permodalan Nasional Madani Cianjur Branch. The research employs a quantitative approach using Structural Equation Modeling (SEM) implemented through the SmartPLS program. The population of interest comprises all employees of PT. Permodalan Nasional Madani Cianjur Branch, with a sample consisting of 102 respondents. Data collection was conducted through online questionnaire distribution, ensuring wide and efficient coverage.The analysis results demonstrate that work motivation plays a significant role in mediating the influence of organizational culture on employee performance at PT. Permodalan Nasional Madani Cianjur Branch. This finding underscores the importance of work motivation as an intervening variable in the relationship between organizational culture and employee performance.The Direct Effect Analysis yielded several important findings. First, the relationship between Organizational Culture (OC) and Work Motivation (WM) shows positive and significant results, with an Original Sample (Path) value of 0.693, t-Statistics of 10.788, and P-Values of 0.000. This indicates that organizational culture has a strong and direct influence on employee work motivation.Second, the relationship between Organizational Culture (OC) and Employee Performance (EP) also shows positive results, albeit with a lower level of significance. The Original Sample (Path) value of 0.068, t-Statistics of 1.949, and P-Values of 0.052 indicate a positive influence, though at the threshold of statistical significance.Lastly, the relationship between Work Motivation (WM) and Employee Performance (EP) demonstrates highly positive and significant results. With an Original Sample (Path) value of 0.760, t-Statistics of 13.294, and P-Values of 0.000, this finding affirms the crucial role of work motivation in enhancing employee performance.In conclusion, this research highlights the importance of organizational culture and work motivation in the context of employee performance at PT. Permodalan Nasional Madani Cianjur Branch. These findings provide valuable insights for management in designing strategies to improve employee performance through strengthening organizational culture and enhancing work motivation.